ANALISIS KUALITAS SOAL MATEMATIKA UJIAN SEKOLAH KELAS XII IPA SMA NEGERI DI WATANSOPPENG BERDASARKAN TEORI RESPON BUTIR - Hasnah, Hasnah (Universitas Negeri Makassar, 2017)
This study aims at describing the quality of mathematics school examination in class XII IPA (Science) at SMAN in Watansoppeng based on theretical aspects (content), 1 Parameter, 2 Parameters, and 3 Parameters. This research is kind of quantitative descriptive research. The subjects of this research were all the participants’ resposes to mathematics school examination of class XII IPA at SMAN in Watansoppeng for 339 answer shets. The data collection was obtained with documentation. The data analysis technique used was quantitative descriptive analysis. The result of the research reveals that mathematics school examination has already fulfilled content validity. In 1 Parameter Logistic Model, the level of difficulty is 22.5% items which is in good category and 77.5% is in poor category. Mathematics school examination in class XII IPA at SMAN in Watansoppeng provides maximal information if it given to the participants who have the ability range -4 to -2. Based on 2 Parameter Logistic Model, the level of difficulty is 37.5% items which is in good category and 62.5% is in poor category. On the aspect distinction power, 50% is in good category an 50% is in poor category. Mathematics school examination in class XII IPA at SMAN in Watansoppeng provides maximal information if it is given to the participants who have the ability of -1. Based on 3 Parameter Logistic Model, the difficulty aspect is 65% which is in good category and 35% is in poor category. On the aspect of distinction power, 47.5% is in good category and 52.5% is in poor category. On guesses parameter, 60% items are in good category and 40% is in poor category. Mathematics school examination in XII IPA at SMAN in Watansoppeng provides maximal information if it is given to the participants who have the ability around -0.2.